A model for the development of women's social entrepreneurship in Bandung City to enhance performance - Harsono, Deti Mulyo; Hasyim, Irsanti; Istiharini, Istiharini; Farman, Fanji Farman; Irawan, Yeremias Budi (Journal of Business and Information Systems (e-ISSN: 2685-2543), 2025)
This research investigates the growth of social entrepreneurship among women in Bandung, Indonesia, to improve the performance of Micro, Small, and Medium Enterprises (MSMEs). It emphasizes the vital importance of women's involvement in the economy, especially in times of economic uncertainty, and evaluates several governmental efforts to empower female entrepreneurs. Utilizing Partial Least Squares (PLS) analysis, the research investigates the impact of motivation and social support on business performance. The study involves a survey of women social entrepreneurs in Bandung, supplemented by in-depth interviews and focus group discussions with experts from government, academia, and business sectors. The results indicate that both motivation and social support have a significant positive effect on business performance, with an R² value of 0.680, suggesting that these factors explain 68% of the variance in business performance. The validity and reliability of the indicators used were confirmed, showing good predictive relevance for business performance. This research contributes to understanding women's social entrepreneurship in Indonesia by providing insights into the motivational and social dynamics that enhance MSME performance. It emphasizes the importance of social support systems and motivation in fostering female entrepreneurship and its impact on the local economy.